The Institutional Determinants of Postgraduate Research Output among Students in Moi University School of Education, Kenya - Kipchirchir , Rotich Hillary (African Journal of Education,Science and Technology (AJEST), 2015)
Research is an important and necessary part of modern university education; Univesities are considered as producers of new knowledge. The Kenyan universities and other universities in developing countries have been rightly accused of giving more focus to teaching than research. The role of postgraduate students in the life and growth of universities cannot be over-estimated. Universites should therefore encourage both individual student authorship and joint authorship by academics and postgraduate research students in appropriate levels. Based on a study conducted in the School of Education of Moi University, this paper focuses on the institutional factors that impact on the quality and quantity of research output by postgraduate students in Kenya. The study sought to investigate the factors that influence research output among postgraduate students‘ in Kenyan public universities in order to provide suggestions that will make universities more productive organizations. The study employed a descriptive survey design. The research used stratified random sampling and purposive sampling. The study involved all the 4 departments within the School of Education. A total of 285 postgraduates were selected out of an accessible population of 1148. Eight (8) postgraduate alumnae and three (3) HODs‘ were also included in the study. Data was collected using questionnaires, interview schedules and document analysis. Data was analysed qualitatively and quantitatively. The findings of the study revealed that institutional factors explained the low research output among postgraduate students in Kenyan public universities. The researcher recommends that the university review its research policies to adequately gather for postgraduates‘ needs. Postgraduates form the highest constituency of public universities and it is time the research output is seriously interrogated.